ANALISIS PENGENDALIAN INTERNAL PIUTANG DAGANG UD. FAISAL BULANMAS 1 KABUPATEN BARITO KUALA - Nor Winda Sari; Amalia, Wia Rizqi (SINERGI : Jurnal Riset Ilmiah, 2025)
Accounts receivable, as one of the current assets of a trading company, is an important asset because it shows the amount of income received. A very large amount of receivables causes the percentage of uncollectible receivables to also be quite large. Therefore, it is necessary to have effective control so that fraudulent acts on trade receivables can be reduced. The internal control system is policies and procedures that protect assets from misuse. This research aims to find out how to implement the internal control system for trade receivables in minimizing uncollectible receivables at UD. Faisal Bulanmas 1, Sugara Island Village, Barito Kuala Regency. By using data collection techniques in the form of interviews and field observations, it can be concluded that the problem of bad debts at UD. Faisal Bulanmas 1 can arise from various aspects, such as technical aspects and debtor negligence. Apart from that, the problem of bad debts can occur due to employees themselves (fraud) or fraud where salesmen commit skimming fraud, namely when customers pay by check or cash, the check or cash will go into their personal pockets. Overall, the internal control system for UD. Faisal Bulanmas 1 runs well even though it is manual based and does not use adequate information technology.